2002
DOI: 10.3346/jkms.2002.17.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Cleft lip and Palate Incidence Among the Live Births in the Republic of Korea

Abstract: We present an epidemiologic study of cleft lip and palate in the Republic of Korea from January 1, 1993 through December 31, 1993. In 1993, the number of total live births was 715,817. And from 1993 through 1995, a total of 1,293 new patients with cleft lip and palate who were born in 1993 were identified. The incidence of cleft lip and palate was 1.81 per 1000, that is, 1 per 554 live births. The cleft lip: cleft lip and palate: cleft palate alone ratio was 1.13:1:1.19. The male: female ratio was 2.1:1 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
52
3
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 9 publications
11
52
3
6
Order By: Relevance
“…56% Females and 44 % males) [21]. Sex ratios were recorded as 2:1, 1.62 &1.41:1 in the study conducted in Dehradun, Gujarat & Republic of Korea [3,16,17]. It was found that most of cleft cases 54.6% were having income of less than Rs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…56% Females and 44 % males) [21]. Sex ratios were recorded as 2:1, 1.62 &1.41:1 in the study conducted in Dehradun, Gujarat & Republic of Korea [3,16,17]. It was found that most of cleft cases 54.6% were having income of less than Rs.…”
Section: Discussionmentioning
confidence: 90%
“…The study conducted in Japan revealed that frequency of CLP>CP>CL, in Scotland CP>CLP>CL, in Republic CP>CL>CLP and in Andhra Pradesh CL>CLP>CP [15,17,20,21]. The sex ratio in CL, CLP, CP and rare clefts were 1.34:1, 1.28:1, 1.12:1 and 0.75:1 respectively but in a study of Republic of Korea the sex ratios were 2.1:1 in CL, 2.5:1 in CLP and 0.95:1 in CP [17].…”
Section: Discussionmentioning
confidence: 99%
“…Female dominance, however, has been identified both elsewhere in the U.K. (Table 1) and worldwide, as confirmed in Bolivia (McLeod et al, 2004), U.S.A (Shapira et al, 1999), Faroe Islands, Greenland and Denmark (Jakobsen et al, 2003), Australia (Vallino-Napoli et al, 2004), Jordan (Al- Omari and Al-Omari, 2004), and Pakistan (Elahi et al, 2004). Kim et al (2002), however, reported CP to have a male dominance in the Republic of Korea (Kim et al, 2002), although this may be related to the short time frame of the study.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to these rates, Altunhan et al (2012) have recently detected the following in Konya Turkey, Central Anatolia, in 121 babies: 86 (71%) CL/P and 35 (29%) CP. The percentages of CL and CL/P in our study is different form studies in The Netherlands (CL 21, CL/P 46, CP 33%) and Korea (CL 21, CL/P 46, CP 33%), and these malformations are also more common in female Pakistani subjects (CL 42, CP and CL/P 34%) (Cornel et al, 1992;Kim et al, 2002;Elahi et al, 2004).…”
Section: Discussionmentioning
confidence: 79%